Squaramide‐Linked Chloramphenicol Base Hybrid Catalysts for the Asymmetric Michael Addition of 2, 3‐Dihydrobenzofuran‐2‐carboxylates to Nitroolefins. Issue 1 (5th January 2018) - Yan, Linjie; Huang, Guanxin; Wang, Haifeng; Xiong, Fangjun; Peng, Haihui; Chen, Fener
Abstract : An array of hybrid catalysts incorporating a chloramphenicol base moiety linked to another chiral scaffold through a squaramide linker were developed and successfully used in the Michael addition of 2, 3‐dihydrobenzofuran‐2‐carboxylates to nitroolefins. Control experiments suggested that the hybrid catalysts were more reactive than nonhybridized bifunctional catalysts, and matching of the chirality between the two scaffolds was crucial for high reactivity and stereoselectivity. These hybrid organocatalysts could be used with a variety of substrates. At a 0.5 mol‐% catalyst loading, a range of 2, 3‐dihydrobenzofuran‐2‐carboxylates derivatives bearing quaternary and tertiary stereogenic centers were obtained in high yields (up to 98 %) with excellent enantioselectivities (up to 99 %  ee ) and moderate diastereoselectivities (up to 8:92 dr ). Abstract : Hybrid catalysts with a chloramphenicol base moiety linked through a squaramide to another chiral scaffold are developed and successfully used in the Michael addition of 2, 3‐dihydrobenzofuran‐2‐carboxylates to nitroolefins. Products bearing quaternary and tertiary stereogenic centers are obtained in high yields with excellent enantioselectivities and moderate diastereoselectivities.